(untitled) (Филологические заметки, 2019)
This paper is based on the multi-semantic potential of the word “essay”,with special emphasis on two meanings: examine and effort. Consequently, from it we can derive two mutually conditioned terms: examination and creating, both representing incompleteness and imperfection, certain perpetual delay. Furthermore,by inspecting Montaigne’s erudition as well as writing style and thought (by immersion in different texts), relationship between reading and humanistic (self)education is observed as unintentional act. In regard to the notion that (self)education implies (self)formation with text as the mediator (in broadest sense),the paper is following Montagine’s several times expressed doubt in subject’s selfsufficiency,emphasizing the question of depersonalization under the burden of quotation.